Association between CTLA-4 Gene Polymorphism and Risk of Hepatocellular Carcinoma in Chronic Hepatitis B Patients - Siregar, Gontar Alamsyah; Tala, Zaimah Z. (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Hepatocellular carcinoma (HCC) is the most common form of liver cancer; most cases of HCC (approximately 80%) are associated with chronic hepatitis B virus (HBV. The HBV-related incidence of HCC is projected to increase for several decades, because of the high prevalence of chronic HBV infection and prolonged latency to HCC development. As of late, studies concerning the connection between CTLA-4 polymorphisms and a few infections definitely stand out. Associaton CTLA-4- 1661G> A had ever been reported in autoimun cases. But the association of CTLA-4-1661G>A polymorphism with HCC and Chronic Hepatitis B risk is hardly reported. Method: The study was conducted in May – November 2020 at Haji Adam Malik General Hospital, Medan, Indonesia. A total of 80 individual were analyzed with case control study. The data analysis was performed with SPSS 18.0 software. Odds ratio (OR) with 95% confidence interval (CI) were used to evaluate the association of CTLA-4 polymorphism with the risk of HCC and Chronic hepatitis B, which was calculated by chi-squared independent test. The examination of CTLA-4 -1661G> polymorphism with real time PCR method. Genomic DNA was extracted from 5 ml frozen whole blood using the DNA Extraction Kit (Qiagen, Germany) according to the manufacturer’s protocol. Result: The distribution of the characteristics of patients with Hepatocellular Carcinoma(HCC) with a mean age (56.98 ± 12,05) and Hepatitis B (45,95 ± 11,02) with the most orientation for HCC was male(77,5%) and for Chronic Hepatitis B was female (47,5%).The most common BCLC stage in HCC is stage D ( 45%). The result demonstrated that frequencies of hemozyous genotype GG,allele and G were remarkably higher in Hepatocellular Carcinoma Group than Chronic Hepatitis B Group (30% vs 2,5%, 70% vs 97,5%,55% vs 33,75%) while hemozyous genotype GA+AA, allele A were remarkably higher in Chronic Hepatitis B Group than Hepatocellular Carcinoma Group ( 97,5% vs 70%, 66,25% 45%). Conclusion: In this study, The CTLA4-1661G>A polymorphism is associated with the incidence of Hepatocellular Carcinoma in chronic hepatitis B patients.